82 Application of Precision Sensor Technologies, Real-time Data Analytics, and Dynamic Models on Extensive Western Rangeland Grazing Systems. (8th October 2021) - Menendez, Hector M; Brennan, Jameson
Abstract: Approximately 40% of the land use within the Northern Great Plains is dedicated to livestock production, with much of the 89.9 million head of cattle and calves in the U.S. concentrated in this area. Precision livestock management has ushered in a new era of sensors and technology to monitor individual animal's health, reproductive, and nutritional status in real-time to improve efficiency. Despite these advances, most of the research has been conducted on dairy operations or within feedlot settings. Incorporation on extensive rangeland production systems remains relatively absent (Brennan et al., 2021). This is primarily due to difficulties in studying animals on rangelands caused by heterogeneity of forage resources, variable environmental conditions, and challenges associated with accessing information across vast distances, often without cellular or internet connection. Advances in communication technology are increasingly connecting remote areas, creating new opportunities to improve livestock production efficiency on extensive rangelands using precision technology. Numerous challenges still exist, including applying and integrating multiple technologies across platforms, effectiveness in a real-world setting, technical skills, and knowledge to utilize real-time data, and achieving economic return for livestock producers. Specifically, we discuss the application of precision technologies and mathematical models for improving ruminant nutrition in rangeland systems (Menendez and Tedeschi, 2020). Opportunities exist to refine or develop the next generation of equations/models that more adequately represent nutrient dynamics such as diet selection, supplementation, movement, behavior, water intake, feed conversion efficiency, heat/cold stress, and gain on an individual animal basis. However, effective adoption and adaptability of new technologies/data analytics merit the consideration of potential intended-and-unintended consequences, such as producer dependency on complex hardware and software systems. Hence, precision capabilities coupled with mathematical models are likely the next step to substantially enhance livestock performance in extensive systems when coupled with feasible and reliable long-term strategies.